Mount Fuji Sign: A Rare Complication of Meningitis - Gönül Şengöz; Filiz Pehlivanoğlu; Mustafa Ali Akçetin (Haseki Tıp Bülteni)

(untitled)
Acute bacterial meningitis is a critical condition also because of associated complications and sequelae besides being a life-threatening infection. The complications may develop due to disease itself, diagnostic procedures or treatment. Pneumocephaly is defined as the presence of air in the cranial cavity. Pneumocephalus of spinal origin may be associated with spinal trauma, penetrating injury, tumors, and infections resulting from iatrogenic causes such as lumbar puncture. Here, we present a case of a 22-year-old male with the diagnosis of acute bacterial meningitis in whom pneumocephalus occurred after lumbar puncture. In this study, we aimed to draw attention to a rare complication of lumbar puncture.